เภสัชจลนศาสตร์ของสารสกัดมาตรฐานบัวบกอีซีเอ 233 หลังการรับประทานแบบครั้งเดียวและหลายครั้งติดต่อกันในหนูแรท - บัณฑิตา พรหมจำรัส (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The standardized extract of Centella asiatica ECa 233 (ECa 233) containing mainly madecassoside and asiaticoside. Pharmacological evaluation of ECa 233 in animals demonstrated positive effect on learning and memory. ECa 233 has been found to exhibit a favorable safety profile. However, information on pharmacokinetics of ECa 233 is not currently available. The aim of this study was to investigate the pharmacokinetic profiles of ECa 233 after oral administration in rats. Male Sprague-Dawley rat received ECa 233 at single dose (30 or 60 mg/kg) and multiple doses for 7 days (30 or 60 mg/kg twice daily) by oral administration. Madecassic acid levels in plasma were determined by validated high performance liquid chromatography method. The concentrations of madecassic acid were linearly related to the response in the range of 0.6-24 µg/ml and the lower limit of quantification (LLOQ) was 0.6 µg/ml. The intra-day and inter-day accuracy and precision in term of % bias and % RSD were less than 10 %. The extraction recoveries of madecassic acid was not less than 90 %. No endogenous interference was detected. The method was applied to pharmacokinetic studies of ECa 233. After single oral administration of 30 and 60 mg/kg of ECa 233, the main pharmacokinetic parameters obtained were: T[max], 2.25 and 4 h; C[max], 1.16 and 3.80 µg/ml; AUC[0-24h, 1.83 and 9.34 µg.h/ml; and t[1/2], 0.54 and 0.96 h, respectively. However, after multiple doses administration with both 30 and 60 mg/kg, AUC0-24h and t1/2 were higher than those observed after single dose administration, indicating that madecassic acid was possibly accumulated. Preliminary pharmacokinetic profiles obtained in the present study is expected to be further pharmacokinetic or pharmacodynamic studies of ECa 233.